2021
DOI: 10.1371/journal.pntd.0009244
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy for detecting Schistosoma japonicum and S. mekongi in humans: A systematic review and meta-analysis

Abstract: Background Most of national schistosomiasis elimination programmes in Asia are relying on stool examination, particularly Kato Katz stool examination technique for regular transmission monitoring. However, the Kato-Katz technique has shown low sensitivity for the detection of light-intensity infections, and therefore highly sensitive diagnostic tools are urgently required to monitor prevalence of infection in low transmission settings. The objective of this systematic review was to evaluate and synthesize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
0
21
0
2
Order By: Relevance
“…The results from our study showed the overall diagnostic performance of PCR had an average high sensitivity of 91% and specificity of 85% with the diagnostic odds ratio of 58. This was considerably higher than the estimates reported in two previous meta-analyses [ 34 , 61 ], of which the former [ 34 ] included four studies only, and the latter [ 61 ] was based on various biological materials and from different host species including serum, feces, urine and saliva from humans, feces from pigs and tissues from snails. Our results suggests that these PCR techniques can be used as an effective tool for diagnosing S .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The results from our study showed the overall diagnostic performance of PCR had an average high sensitivity of 91% and specificity of 85% with the diagnostic odds ratio of 58. This was considerably higher than the estimates reported in two previous meta-analyses [ 34 , 61 ], of which the former [ 34 ] included four studies only, and the latter [ 61 ] was based on various biological materials and from different host species including serum, feces, urine and saliva from humans, feces from pigs and tissues from snails. Our results suggests that these PCR techniques can be used as an effective tool for diagnosing S .…”
Section: Discussionmentioning
confidence: 57%
“…As a range of protocols, and/or different biological samples, have been used for PCR diagnoses of schistosome infections, the reported diagnostic performances or estimates of such techniques have therefore also varied greatly [33]. Whilst many studies find PCR to be highly specific and sensitive, PCR diagnostic accuracies have been reported to be considerably lower than the commonly used indirect hemagglutination assay [34]. Therefore, we performed a meta-analysis of data from studies using PCRs on DNA extracted from human serum or stools, to evaluate the overall diagnostic value of variable-temperature PCR technology for S. japonicum infections in terms of comprehensive indexes, when compared to the conventional Kato-Katz method.…”
Section: Introductionmentioning
confidence: 99%
“…Stability is also a crucial factor in evaluating a method, especially in different conditions of carriage, storage, and experimental environments. Unfortunately, contrasting results occurred in some studies [ 18 , 71 , 146 ], suggesting that the developed approaches should be evaluated in a multicenter manner. Carry-over contamination is another nerve-wracking problem, especially for isothermal amplification techniques with higher sensitivity [ 51 , 112 ].…”
Section: Chance Challenges and The Way Forwardmentioning
confidence: 99%
“…In addition, their shortcomings such as missing early or light infections became obvious with the decrease of prevalence and infection intensity in endemic areas [ 19 ]. More sensitive and rapid tools are needed emergently for schistosomiasis surveillance and quick response [ 20 , 21 ]. Molecular xenomonitoring is an alternative approach to detect pathogens in their vectors, which had been reported for monitoring the transmission of parasitic diseases, such as malaria, filariasis, sleeping sickness as well as schistosomiasis, etc.…”
Section: Introductionmentioning
confidence: 99%